(untitled) (Global Journal of Management and Business Research, 2019)
As the number of travelers around the world grows the importance of managing tourism destinations sustainably becomes increasingly important This study has been conducted to identify the behavior of tourists towards its necessity of sustainable measures in a tourist destination The data have been collected through a self-structured questionnaire 0702 from 160 tourists that have been randomly chosen from Cox s-Bazar Bangladesh August to September 2018 From the correlation analysis it has been found that both age r 224 and education r 150 has a very weak but positive relationship with the consciousness of sustainable tourism This study also revealed that all the respondents either male or female have very good attitudes towards sustainable initiatives though few of them have a negative attitude due to lack of proper notice Initiatives like promotional activities may play a great role to increase the positive attitudes of tourist regarding sustainable tourism This study is expected to aid in marketing and retention efforts for sustainable tourism as well as future direction for the development of sustainable tourism